Royal Jelly Plus Coenzyme Q10 Supplementation Enhances High-Intensity Interval Exercise Performance via Alterations in Cardiac Autonomic Regulation and Blood Lactate Concentration in Runners - Ovchinnikov, Aleksandr N.; Deryugina, Anna V.; Paoli, Antonio (Frontiers in Nutrition, 2022)
Purpose: This study aimed to examine whether oral royal jelly (RJ) and coenzyme Q10 (CoQ10) co-supplementation could improve high-intensity interval exercise (HIIE) performance in runners, reducing exercise-induced lactic acidosis and decreasing elevated sympathetic tone following exercise. Methods: Thirty regional-level runners (age: 19±1 years; height: 173±2 cm; body mass: 68.9±2 kg; body mass index: 23.1±1 kg/m2) were randomly allocated to receive either 400 mg of RJ and 60 mg of CoQ10 (RJQ) or matching placebo (PLA) once daily for 10 days. Exercise performance expressed as time taken to complete HIIE was evaluated at baseline, and then reassessed at day 10 of intervention. HIIE protocol applied to the runners included 3 repetitions of 100 m distance at maximum possible speed interspersed with 45 s of recovery periods. Indices of heart rate variability and blood lactate concentration were also measured before and immediately after HIIE in each group. Results: HIIE performance significantly improved in RJQ group (p = 0.005) compared to PLA group. Blood lactate levels and sympathetic influence on the heart were significantly lower both before and after the HIIE in athletes who received RJQ (p<0.05) compared to PLA. Regression analysis showed that oral RJQ administration for 10 days was significantly associated with reductions in HIIE-induced increases in blood lactate concentration and enhanced cardiac parasympathetic modulation following exercise compared to PLA. Principal component analysis revealed that runners treated with RJQ are grouped by the first two principal components into a separate cluster compared to PLA. Correlation analysis demonstrated that the improvements in runners’ HIIE performance were due in significant part to RJQ-induced reducing the increment in blood lactate levels in response to exercise in combination with a more rapid shift in autonomic activity toward increased parasympathetic control early at postexercise. Conclusions: These findings suggest that RJQ supplementation for 10 days is potentially effective for enhancing HIIE performance and alleviating adverse effects of increased intramuscular acidity and prolonged sympathetic dominance following intense exercise.